Navigating complexity in action. The 7 C Model: awareness, complexity, context, culture, capabilities, conversations and strategic concretization (Ágora de Heterodoxias, 2026)
This article presents the results of the research “Navigating Complexity in Action: The 7C Model. Awareness. Complexity. Context. Culture. Capabilities. Conversations. Strategic Concretization”. The objective was to propose a management model useful in complex and uncertain contexts. The method employed was based on the emerging humanistic-scientific paradigm and complex thinking. The study was exploratory, qualitative, and propositional. The methodology consisted of a theoretical review of classical management contrasting with emerging categories from different disciplines, preliminary design of the model, validation through expert consultation, and redesign. It is concluded that both the current challenges in complex, hypercomplex, and uncertain contexts, and the advances in different disciplines of knowledge require new ways of approaching managerial practice that integrate multiple perspectives, methods, and tools. The 7C Model constitutes one such approach.
Keywords: complexity; uncertainty; complexity management; conscious leadership; systemic resilience